2021
DOI: 10.15548/mej.v5i2.3056
|View full text |Cite
|
Sign up to set email alerts
|

Kemampuan Berpikir Kreatif Matematis Siswa SMP Dalam Menyelesaikan Soal Problem Posing

Abstract: The Ministry of Education and Culture (2016) states that one of the learning objectives in the 2013 curriculum is to develop creative activities that involve imagination, intuition, and discovery by developing divergent, original thinking, curiosity, making predictions and guesses, and experimenting. The fact that the creative thinking ability of Indonesian students is still low is shown in the results of the Program for International Student Assessment (PISA) in mathematical ability, placing Indonesia at 62 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The interviews showed that four subjects had difficulty visualizing the problems given and could not predict the later pattern. It is in line with research showing that creativity in generating ideas and developing information obtained is still low (Aba et al, 2021).…”
Section: Formulatingsupporting
confidence: 89%
“…The interviews showed that four subjects had difficulty visualizing the problems given and could not predict the later pattern. It is in line with research showing that creativity in generating ideas and developing information obtained is still low (Aba et al, 2021).…”
Section: Formulatingsupporting
confidence: 89%